Alat Peringatan Dini Bencana Tanah Longsor Dengan Metode Geolistrik - Rachmat Setiawibawa; Dekki Widiatmoko; Rafi Maulana Al-Farizi; Eriski Prawira (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Resistivity or resistivity of the soil. Earth is assumed to be a sphere that is isotropically homogeneous. With this assumption, the measured resistivity is the true resistivity and is independent of the electrode spacing. But in reality the earth consists of different layers so that the measured potential is the effect of these layers. Then the measured resistivity value is not just a single layer resistivity value, but several layers, this is especially true for wide electrode spacing.